What is Your Reference Point? How Price Volatility and Organizational Context Affect the Reference Points of Family and Nonfamily Managers - Evelyn Stommel; Nicole Gottschalck; Andreas Hack; Kimberly A. Eddleston; Franz Kellermanns; Nils Kraiczy (Small Business Economics, 2024)
Abstract Drawing from prospect theory, we use an experimental study design to explore how and why reference points of managers of family and nonfamily firms differ. We contribute to research on the role of economic theories for family businesses by elaborating on decision-making mechanisms in the context of family firms. Furthermore, we investigate whether family and nonfamily managers within family firms vary in their investment decisions. Our study demonstrates the importance of price volatility as a determinant of reference points and shows how the same type of information can lead to different reference points based on whether the manager is from a family or nonfamily firm.
Additional information: D81;D84
Keywords: 330; Family business; Prospect theory; Reference points; Investment decisions; Family firms; Reference point; Price volatility; Family managers; Non-family managers